2019
DOI: 10.1016/j.jcta.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Structural submodularity and tangles in abstract separation systems

Abstract: We prove a tree-of-tangles theorem and a tangle-tree duality theorem for abstract separation systems → S that are submodular in the structural sense that, for every pair of oriented separations, → S contains either their meet or their join defined in some universe U of separations containing → S . This holds, and is widely used, if U comes with a submodular order function and → S consists of all its separations up to some fixed order. Our result is that for the proofs of these two theorems, which are central t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…For a full introduction to abstract tangle theory and its terminology and notation we refer the reader to [2,4]. In the remainder of this section we offer a brief introduction of only those terms and notation of tangle theory that are relevant to this paper.…”
Section: Separation Systems and Profilesmentioning
confidence: 99%
See 3 more Smart Citations
“…For a full introduction to abstract tangle theory and its terminology and notation we refer the reader to [2,4]. In the remainder of this section we offer a brief introduction of only those terms and notation of tangle theory that are relevant to this paper.…”
Section: Separation Systems and Profilesmentioning
confidence: 99%
“…Later Diestel, Erde, and Weißauer [4] showed that the latter structural condition by itself is already sufficiently strong for proving tree-of-tangles theorems: tangle theory can be meaningfully studied without the hitherto usual assumption of a submodular order function, further widening its applicability. If a separation system has this structural property but not necessarily a submodular order function then it is structurally submodular or simply submodular if the context is clear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theorem 15. Let − → S be a separable 4 submodular separation system in some universe of separations, let F ⊆ 2 − → S contain P S , and let F * be any uncrossing of F. Then the following are equivalent: 4 Whilst the assumption that − → S is separable is necessary to apply Theorem 5, in a forthcoming paper [6] the authors and Weißauer show that every submodular separation system is in fact separable, and so this asssumption can be removed from Theorem 15.…”
Section: A Duality Theorem For Abstract Profilesmentioning
confidence: 99%